Study on Deterioration Effect of Dynamic Mechanical Properties of Granite at Subzero Temperatures. (28th June 2022) - Yang, Yang; Wang, Jianguo
Abstract : In the present work, through the dynamic impact test of frozen granite, the effect of temperature on the dynamic mechanical performances of granite at high strain rates were investigated. Based on the existing energy and damage theory, the effects of different low temperatures on the energy dissipation, damage variables, and strength of red sandstone are explored. The reasons for the deterioration of granite dynamic mechanical strength at low temperature are studied by combining analyses of fracture morphology. Researched results showed that low temperatures (<-20°C) cause "frostbite" in granite, leading to the sharp decrease of dynamic and macromechanical strength of the rock under a high strain. Under this dynamic disturbance, transient engineering disasters are easy to occur. The analysis of fracture morphology showed that the lower negative temperature results in the formation of cracks among the mineral particles in the granite. Under high strain rate loading, these cracks have poor plastic deformation ability and are easily destabilized and expanded. Moreover, frozen granite tends to be brittle as a whole. With the decrease of negative temperature, its fracture behavior gradually changes from cleavage fracture to transgranular fracture, and the failure mode also changes from tensile failure to shear failure. The coupling effect of impact and the lower negative temperature will cause the quasicleavage of some crystalline minerals, eventually leading to low-stress brittle failure of granite.